Bandgap engineering in SrTiO3 thin films by electronic excitations: A synchrotron-based spectroscopic study. (1st April 2021) - Kumar, Vishnu; Bhogra, Anuradha; Bala, Manju; Kuo, Hung-Wei; Chen, Chi-Liang; Dong, Chung-Li; Kandasami, Asokan; Subramanian, Annapoorni
Abstract: Engineering the optical bandgap of metal oxides is essential for optoelectronic and photocatalytic applications. The present study reports the application of electronic excitations, induced by 125 MeV Ag ions, in tuning the bandgap of SrTiO3 films in the range of 2.93-3.78 eV and their correlation with the synchrotron-based X-ray diffraction pattern and X-ray absorption spectra (XAS). The pre-edge spectral features in the XAS at Ti K -edge show significant variation in the valence state implying the role of electronic excitations in modifying the local electronic structures mainly the distortion in the TiO6 octahedra and the ratio of area under t 2g / e g . This study gives an insight about the role of structural properties and electronic structures in bandgap tuning. Graphical abstract: Image, graphical abstract